2017
DOI: 10.1063/1.5011728
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field response of doubly clamped magnetoelectric microelectromechanical AlN-FeCo resonators

Abstract: Magnetoelectric (ME) cantilever resonators have been successfully employed as magnetic sensors to measure low magnetic fields; however, high relative resolution enabling magnetometry in high magnetic fields is lacking. Here, we present on-chip silicon based ME microelectromechanical (MEMS) doubly clamped resonators which can be utilized as high sensitivity, low power magnetic sensors. The resonator is a fully suspended thin film ME heterostructure composed of an active magnetoelastic layer (Fe0.3Co0.7), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…The delta-E effect of the Young’s modulus has especially been studied thoroughly in soft magnetic amorphous materials [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. It was used for magnetic field sensing with magnetoelectric plate resonators [ 19 , 20 , 21 , 22 ] and beam structures [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Such resonators are operated in bending or bulk modes and some have achieved limits of detection down to the sub-nT regime at low frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…The delta-E effect of the Young’s modulus has especially been studied thoroughly in soft magnetic amorphous materials [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. It was used for magnetic field sensing with magnetoelectric plate resonators [ 19 , 20 , 21 , 22 ] and beam structures [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Such resonators are operated in bending or bulk modes and some have achieved limits of detection down to the sub-nT regime at low frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [6] designed and fabricated strain-sensitive spin valves with a composite Fe-Ga/Fe-Co layer on a flexible substrate. Bennett et al [7] demonstrated the doubly clamped resonator design as a magnetoelectric aluminum nitride/Fe-Co thin film heterostructure. Wang et al [8] also demonstrated the magnetostrictive effect of Fe-Co thin films on a lithium niobate substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, we calculate the intrinsic magnetic noise (b n ) of the magnetic sensor, which is determined by the thermomechanical noise, as expressed by [25],…”
Section: Resultsmentioning
confidence: 99%